THE IMPACT OF VITAMIN B6 ON PREVENTING POSTPARTUM DEPRESSION - Magdalena Próchnicka,; Dominika Nowak,; Michał Siwek,; Adam Zarzycki,; Jan Noskowicz,; Jan Urban,; Jakub Hamouta,; Patrycja Długosz,; Julia Konat,; Wiktor Doroszuk, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Postpartum depression (PPD) is one of the most common complications of childbirth. Globally, PPD afflicts up to approximately twenty percent of women during pregnancy or after giving birth. Untreated postpartum depression can have substantial adverse effects on the well-being of the mother and child, negatively impacting child cognitive, behavioral, and emotional development with lasting consequences. The aim of this review is to summarize current evidence on vitamin’s B6 role on preventing postpartum depression.Material and methods: A PubMed literature serach was conducted using terms ”vitamin B6 in postpartum depression”, ”postpartum mood disorders”, and ”vitamin B6 and pregnancy”. Filters included Free Full Text, Clinical Trial, Randomized Clinical Trial, within the last 10 years.Results: This single-blind, placebo-controlled clinical trial was conducted on 81 pregnant women who were at risk of PPD. They received 80 mg of vitamin B6 daily and placebo, respectively from the 28th week until the end of pregnancy. The risk of PPD was assessed as the main inclusion criteria using a structured clinical interview using hospital anxiety-depressive scale, social support appraisals scale, and Holmes and Rahe life change and stress evaluation questionnaire. It was found that the mean score of depression in the post-intervention group was significantly lower than that of the pre-intervention group.Conclusions: According to the obtained results, vitamin B6 has a positive effect on reducing postpartum depression scores among mothers at risk for PPD. However, these arrangements should be seen as preliminary, until treatment is assessed in larger, multicentre studies of longer duration.